THE INFLUENCE OF REFERENCE GROUPS, TRUST, AND TRADITION ON CUSTOMERS’ DECISION TO USE ISLAMIC GOLD PAWN SERVICE WITH EDUCATION AS A MODERATING VARIABLE - Niken Purnama Santi; Ahmad Habibi; Siska Yuli Anita (JURNAL PROFIT, 2025)
This study aims to analyze the influence of reference groups, trust, and tradition on customers’ decisions to use Islamic gold pawn services, with education as a moderating variable. The research was motivated by the growing public interest in Islamic gold pawn products at Bank Syariah Indonesia (BSI) Tulang Bawang Barat Branch, which is influenced not only by economic factors but also by social, cultural, and educational aspects. The study employed a quantitative associative approach with 59 respondents selected through purposive sampling. Data were collected using an online questionnaire (Google Form) and analyzed with SPSS version 25, including validity and reliability tests, multiple linear regression, and Moderated Regression Analysis (MRA) to examine the role of education as a moderating variable. The findings reveal that reference groups, trust, and tradition have a positive and significant effect on customer decisions, both partially and simultaneously. Among these variables, tradition has the most dominant influence on decision-making. The coefficient of determination (R²) value of 0.812 indicates that 81.2% of the variation in customer decisions is explained by these three variables, while the remaining 18.8% is affected by other factors not examined in this study. The results emphasize that social and cultural factors play a crucial role in shaping customers’ behavior toward Islamic financial products. Therefore, Islamic financial institutions are encouraged to strengthen marketing strategies based on trust, tradition, and financial education to enhance public participation in Islamic pawn services.